1841 Md. Laws 114, An Act To Incorporate The Mount Orange Cemetery, In The County of Baltimore, ch. 148, § 4 - (:unkn) unknown (General Publisher, 1841)
Any Person who shall willfully destroy, mutilate, deface, injure or remove any tomb, monument, grave stone, or other structure, placed in the cemetery . . . or shall shoot or discharge any gun, or other fire arms, within the said limits, shall be considered guilty of a misdemeanor . . .
--
Keywords: DISCHARGE